2018
DOI: 10.1186/s12902-018-0291-x
|View full text |Cite
|
Sign up to set email alerts
|

No changes in levels of bone formation and resorption markers following a broad-spectrum antibiotic course

Abstract: BackgroundIntestinal bacteria influence bone remodeling in rodents, and antibiotic manipulation of the rodent gut microbiota increases bone formation and prevents ovariectomy-induced bone loss. In theory, these effects may be mediated by changes in sex hormone biotransformation in the gut, gut serotonin secretion or nutrition-induced secretion of glucagon-like peptide 2 (GLP-2) and glucose-dependent insulinotropic hormone (GIP). Antibiotics change the human gut microbiota, but the effect of antibiotic treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Similarly, antibiotic treatments have been shown to have a range of effects on bone density; antibiotic-treated mice appear to have higher bone density in some experiments, (12) but other reports include adverse (15,16) or no effects. (17) Finally, a number of experiments have demonstrated that probiotic preparations, commonly including one or more Lactobacillus species, may positively affect mineral metabolism or bone health. (18)(19)(20)(21) Despite the growing series of animal experiments that demonstrate an effect of the gut microbiome on skeletal health, there are very few studies in humans that examine whether there are associations between the gut microbiome and skeletal status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, antibiotic treatments have been shown to have a range of effects on bone density; antibiotic-treated mice appear to have higher bone density in some experiments, (12) but other reports include adverse (15,16) or no effects. (17) Finally, a number of experiments have demonstrated that probiotic preparations, commonly including one or more Lactobacillus species, may positively affect mineral metabolism or bone health. (18)(19)(20)(21) Despite the growing series of animal experiments that demonstrate an effect of the gut microbiome on skeletal health, there are very few studies in humans that examine whether there are associations between the gut microbiome and skeletal status.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, antibiotic treatments have been shown to have a range of effects on bone density; antibiotic‐treated mice appear to have higher bone density in some experiments, ( 12 ) but other reports include adverse ( 15,16 ) or no effects. ( 17 ) Finally, a number of experiments have demonstrated that probiotic preparations, commonly including one or more Lactobacillus species, may positively affect mineral metabolism or bone health. ( 18‐21 )…”
Section: Introductionmentioning
confidence: 99%
“… 42 , 43 Even without the use of a carrier, prolonged use of antibiotics such as gentamycin or vancomycin have been reported to have no impact on bone turnover markers such as carboxy-terminal collagen crosslinks (CTX) or osteocalcin in humans. 45 We have not been able to find any studies reporting a negative effect of long-term antibiotic usage or accumulation in bone with the exception of tetracycline. Recurrence of infection is reduced both in chronic osteomyelitis as well as in PJI, both with non-HA-binding antibiotics such as penicillin 46 or with HA-binding antibiotics such as rifampicin, 47 even with prolonged treatment.…”
Section: Antibiotics In Bone Mineral and Infectionmentioning
confidence: 83%
“…Another study showed that low dose administration of penicillin enhanced the BMD and bone mineral content (BMC) of female C57BL/6J mice ( Cox et al, 2014 ). However, in humans administration of broad spectrum antibiotics did not show any affect on bone health ( Mikkelsen et al, 2018 ).…”
Section: Nexus Between Gut Microbiota and Bone Healthmentioning
confidence: 99%